Board level employee representation in Europe: priorities, power and articulation - Waddington, Jeremy; Conchon, Aline (Abingdon, 2015)
"Board Level Employee Representation in Europe analyses the role, activities and networking of board level employee representatives in sixteen European countries and their counterparts operating in companies that have adopted European status. Board level employee representation is viewed as a key element of worker participation in Europe, but there has been only limited international comparative research that establishes what board level employee representatives do and how their activities vary between countries. Based on a large-scale survey distributed to board level employee representatives (circa more than 4,000 respondents), this study identifies the personal characteristics and industrial location of board level employee representatives, what they do and how they interact with other parties within and outside of the company. This study fills in a knowledge gap at a time when policy debates are considering stakeholder models of corporate governance as a means on the way out of the crisis and the achievement of sustainable economies.